Application of Rabbit Liquid Organic Fertilizer on Intercropping Yield of Onion (Allium Ascalonium, L.) and Soybean (Glycine Max, L.) - Made Sri Yuliartini; Luh Kartini; Sastra Eli Waruwu (Agriwar Journal, 2021)
This study aims to determine the effect of rabbit Liquid Organic Fertilizer (LOF) concentration on the yield of intercropping shallots and soybeans. This research was carried out in rice fields, Tempekan Abianbase Subak Buaji, Denpasar from February to May 2021. The research method used was a simple randomized block design (RBD) with one factor treatment of rabbit LOF consisting of 6 levels, namely UC1 = 25 ml.l-1, UC2 = 50 ml.l-1, UC3 = 75 ml.l-1, UC4 = 100 ml.l-1, UC5 = 125 ml.l-1 and UC6 = 150 ml.l-1 repeated 3 times so that 18 plots are required. The highest fresh weight of tubers per clump and fresh yield of tubers per hectare was obtained at concentrations of 150 ml.l-1, namely 44.50 g and 4.45 tons, increased by 14.72% and 14.69% compared to concentrations of 25 ml.l-1, namely 38.79 g and 3.88 tons. The dry weight of seed harvest per plant and the highest dry yield of seed harvest per hectare was obtained at concentrations of 150 ml.l-1, namely 30.02 g and 4.00 tons, increased by 28.40% and 27.39% compared to the concentration of 50 ml. l-1 are 23.38 g and 3.14 tons. The highest oven dry weight of seeds per plant and oven dry yield per hectare was obtained at concentrations of 150 ml.l-1, namely 22.95 g and 3.06 tons, an increase of 26.86% and 26.97% compared to a concentration of 50 ml.l-1are 18.09 g and 2.41 tons.